UIWGViz: An architecture of user interest-based web graph vizualization. (February 2018) - Saleheen, Shibli; Lai, Wei
Abstract: Visualization improves the user experience by presenting a pictorial view of the web information. Users are benefited in navigating and searching using the web graph visualization because the web graph presents the relationships among the web documents. To achieve this goal, the web information is processed through several steps from the web data collection to the final visualization. Researchers propose and develop various frameworks to systematically accomplish the required steps. However, to make the visualization more effective to the users, their interests or preferences need to be incorporated to the web graph generation procedures. Towards this goal, this paper presents an architecture to produce and visualize the user interest-based web graph (UIWG). The presented architecture establishes the procedures to model the user interests. To construct and manage the user interest profile, the architecture analyses both implicit and explicit user feedbacks. The architecture also presents the steps to collect and analyse the web data and finds out the appropriate positions to incorporate the user interests to the UIWG generation procedures. According to the architecture, the user interests are integrated to the filtering to remove irrelevant web documents, to the graph generation to connect the web documents according to the user, and to the clustering to group web documents that are similar to a specific user. The UIWG is visualized through an interface and the architecture describes the analysis of the user interactions to capture the implicit user feedback. The transformation of the web data throughout various steps of the architecture are also discussed in this paper.